Integrating Ultra-Weak Photon Emission Analysis in Mitochondrial Research - Van Wijk, Roeland; Van Wijk, Eduard P.A.; Pang, Jingxiang; Yang, Meina; Yan, Yu; Han, Jinxiang (Frontiers in Physiology, 2020)
Once regarded solely as the energy source of the cell, nowadays mitochondria are recognized to perform multiple essential functions in addition to energy production. Since the discovery of pathogenic mitochondrial DNA defects in the 1980s, research advances have revealed an increasing number of common human diseases, which share an underlying pathogenesis involving mitochondrial dysfunction. A major factor in this dysfunction is reactive oxygen species (ROS), which influence the mitochondrial-nuclear crosstalk and the link with the epigenome, an influence that provides explanations for pathogenic mechanisms. Regarding these mechanisms, we should take into account that mitochondria produce the majority of ultra-weak photon emission (UPE), an aspect that is often ignored – this type of emission may serve as assay for ROS, thus providing new opportunities for a non-invasive diagnosis of mitochondrial dysfunction. In this article, we overviewed three relevant areas of mitochondria-related research over the period 1960–2020: (a) respiration and energy production, (b) respiration-related production of free radicals and other ROS species, and (c) ultra-weak photon emission in relation to ROS and stress. First, we have outlined how these research areas initially developed independently of each other – following that, our review aims to show their stepwise integration during later stages of development. It is suggested that a further stimulation of research on UPE may have the potential to enhance the progress of modern mitochondrial research and its integration in medicine.